Tarik-Ulur Fomo dan Jomo: Pengaruh Simultan Dua Kekuatan Psikologis terhadap Perilaku Pembelian Generasi Z - Viant Anggi Saputra; Barida Rakhma Nuranti; Zuchdiawati Luthfi Utami; Ayu Diana Ansori; Ardila Dwi Rahma Ningrum (MANABIS: Jurnal Manajemen dan Bisnis, 2026)
This study examines the influence of Fear of Missing Out (FOMO) and Joy of Missing Out (JOMO) within a single integrative model on the purchasing behavior of Generation Z in Indonesia. Using an explanatory quantitative approach with a cross-sectional survey design, data were collected from 200 Gen Z respondents (aged 18–27 years) who actively use social media and have made online purchases. The instruments were adapted from standardized scales: FOMO (6 items, α = 0.85), JOMO (5 items, α = 0.83), and purchasing behavior (7 items, α = 0.87) using a 5-point Likert scale. Multiple linear regression analysis showed that FOMO has a significant positive effect on purchasing behavior (β = 0.275; p < 0.001), whereas JOMO has a significant negative effect (β = -0.396; p < 0.001). The regression model was significant (F = 31.34; p < 0.001) with an R² of 0.241. The absolute value of the JOMO coefficient is larger than that of FOMO, indicating the dominance of the JOMO effect in this sample. This study contributes to the digital consumer behavior literature by integrating two opposing psychological constructs into a single empirical model in Indonesia.